Assessing the effectiveness of Problem Based Learning (PBL) using Quality Function Deployment (QFD): Students Perspective - Mohd. Rohani, Jafri; Abu Hassan, Mohd. Ariffin; Syed Hassan, Syed Ahmad Helmi; Mohd. Yusof, Khairiyah; Abd. Hamid, Mohd. Kamaruddin (2005)
The paradigm shifts from traditional chalk-and-talk teaching method to a more innovative teaching style and method in engineering education is the key in transforming the way engineers are prepared to solve complex problems for the 21st century. Rather than presenting the content first, PBL presents the students with an ill-structured, ambiguous, complex and messy problem and with no clear solution. PBL will increase the student’s comprehension, retention, and application of basic engineering skills. This article demonstrates a case study of how we address the student’s concern in PBL environment for making it successful using QFD approach. This results of this QFD assessment revealed that the major concerned voice by the students should be considered by the lecturer for continuous teaching improvement for making PBL effective.